Segmented capacitance tomography electrodes: A design and experimental verifications - Elmy Johana, Mohamad, Dr.; Ruzairi, Abdul Rahim, Prof. Dr.; Leow, Pei Ling, Dr.; Mohd Hafiz Fazalul, Rahiman, Dr.; Omar Mohd Faizan, Marwah; Nor Muzakkir, Nor Ayob (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org/